1982
DOI: 10.1001/archderm.118.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Papular mucinosis. A clinicopathologic study of four patients

Abstract: Four patients with papular mucinosis were studied. Each patient had clinically characteristic cutaneous lesions, increased dermal deposition of mucin, and a serum monoclonal lgG paraprotein. One patient had sclerodermoid features consistent with the scleromyxedema variant of papular mucinosis. Associated findings in the patients included pachydermoperiostosis (one case), adenocarcinoma of the stomach (one case), carcinoma of the pancreas (one case), bizarre neurologic symptoms (one case), and emphysema (two ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 20 publications
0
24
0
1
Order By: Relevance
“…PUVA, Grenz ray, and electron beam therapy have also been used with mixed results [19]. Variable results have been obtained with systemic steroids [20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32] and daily cyclophosphamide [33, 34]. Pulse cyclophosphamide was effective in 1 patient [35].…”
Section: Discussionmentioning
confidence: 99%
“…PUVA, Grenz ray, and electron beam therapy have also been used with mixed results [19]. Variable results have been obtained with systemic steroids [20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32] and daily cyclophosphamide [33, 34]. Pulse cyclophosphamide was effective in 1 patient [35].…”
Section: Discussionmentioning
confidence: 99%
“…13 It is a rare manifestation of scleromyxedema with only 10 documented cases. [6][7][8]12,13,[39][40][41][42][43] Typically, dermatoneuro syndrome has been treated with intensive care monitoring, [39][40][41] plasmapheresis, 42 IV steroids, 8,12 or combinations of these treatments with variable outcomes. 13,43 Improved mental status has been observed in patients treated with plasmapheresis alone 42 and patients given combined treatment with both plasmapheresis and steroids.…”
Section: Discussionmentioning
confidence: 99%
“…FARMER et al [10] reported two scleromyxoedema patients with pulmonary emphysema in a post-mortem examination, but found no myxoedematous deposits in the pulmonary vessels. FUDMAN et al [5] first reported a diminished DL,CO in pulmonary function tests.…”
Section: Discussionmentioning
confidence: 98%